Mutations in the DNA-binding codons of TP53, which are associated with decreased expression of TRAILreceptor-2, predict for poor survival in diffuse large B-cell lymphoma - Young, Ken H. (American Society of Hematology, 2007)
Mutations of the TP53 tumor suppressor gene have been associated with poor survival in some series of diffuse large B-cell lymphoma (DLBCL) but not in other studies. The purpose of this study was to identify the frequency of TP53 alterations (mutations or deletions), characterize the gene expression of mutant/deleted cases, and determine the effects of mutations on survival. In a series of DLBCL that had previous gene expression profiling, we identified 24 mutations in 113 cases (21%). There was no difference in the frequency of mutations in the molecular subgroups of DLBCL. Twelve (50%) of the 24 cases had mutations localized to the DNA-binding codons in the core domain of TP53. The presence of any TP53 mutation correlated with poor overall survival (OS; P = .044), but DNA-binding mutations were the most significant predictor of poor OS (P < .001). Multivariate analysis confirmed that the International Prognostic Index, tumor size, and TP53 DNA-binding mutations were independent predictors of OS. Gene expression analysis showed that TRAILreceptor-2 (DR5) was the most differentially underexpressed gene in the TP53 mutated cases. Investigation is warranted into targeted therapy toward TRAIL receptor-2, to potentially bypass the adverse effect of mutated TP53 in DLBCL.